FSH-mediated regulation of POSTN expression in ovine granulosa cells via SRF transcription factor - Pei, Linlin; Wang, Wenhao; Guo, Peilin; Duan, Xinhua; Xu, Xin; Liu, Chunjie (Frontiers in Animal Science, 2025)
IntroductionFollicle-stimulating hormone (FSH) plays a crucial role in regulating ovarian follicular development in sheep. This study investigated the regulatory mechanism of FSH in periostin (POSTN) expression in ovine granulosa cells (GCs).MethodsImmunofluorescence staining revealed POSTN expression throughout the cytoplasm and nucleus of the GCs. The treatment of GCs with 10 ng/mL FSH significantly increased POSTN mRNA and protein levels in a time-dependent manner, peaking at 24 h. Knockdown of POSTN using siRNA severely impaired GCs viability, which could not be rescued by FSH, indicating the essential role of POSTN in GCs function. Cloning and analysis of the POSTN promoter identified putative binding sites for serum response factor (SRF) and JunD transcription factors within the core promoter region (-387 to +1). Targeted mutagenesis of the SRF site significantly reduced POSTN transcriptional activity, whereas JunD mutation had no effect. Chromatin immunoprecipitation assays confirmed SRF enrichment at the POSTN promoter following FSH stimulation.Results and DiscussionThese findings indicate that FSH regulates POSTN expression in ovine GCs through the transcription factor SRF, potentially by activating signaling cascades such as cAMP/PKA and MAPK/ERK to promote SRF phosphorylation and activation, a mechanism that remains to be further explored. This study provides new insights into the molecular mechanisms of folliculogenesis and offers a potential target for enhancing reproductive efficiency in sheep.